The Structure-Soil-Structure Interaction Effects on the Response of the Neighbouring Frame Structures - ADA, Mehmet; AYVAZ, Yusuf (Latin American Journal of Solids and Structures, 2019)
The Structure-Soil-Structure Interaction (SSSI) phenomenon between the neighbouring structures has been interested lesser than Soil-Structure Interaction. However, in urban environments, the structures have to be constructed in the neighbourhood, and it is inevitable that these structures affect each other's responses. This study examines the Structure-Soil-Structure Interaction effects on the response of the neighbouring frame structures. In this context, firstly the effects of the consideration of the underlying soil on the response of the structures (3-, 6-and 12-storey) are compared with the fixed base conditions. Subsequently, the variation in the acceleration and basement storey drift ratios of the structures are examined to determine the effects of the presence of the neighbouring different structures. The clear distances between the structures, structure storey numbers, soil stiffness, seismic motion and layout of the structures are the parameters taken into account. Finite element method is utilised to analyse the soil and the structures subjected to seismic excitation with direct method. It is concluded that the consideration of the neighbouring structures could positively or negatively change the responses of the structures based on the dynamic characteristics of the case.